1996
DOI: 10.1007/bf02088573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in rats of the dose-response relationship among colonic mucosal growth, colonic fermentation, and dietary fiber

Abstract: The dose-response relationship among dietary fiber, colonic fermentation, fecal weight, and mucosal growth were evaluated in this study. The morphometric parameter of total mucosal volume was used to assess diet-induced differences in colonic mucosal growth. Dietary fibers with a wide range of fermentability and that have previously been shown to inhibit the development of colonic neoplasia in rats were used. Sprague-Dawley rats were fed Purina Rodent Chow, AIN-76a fiber-free diet, or an AIN-76a diet supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The normal development of the hind gut is the foundation for maintaining barrier function and fermentability (32) . Recent research showed that RPS could increase the weight of the large intestine and the mucosa thicknesses of the caecum in pigs (33) .…”
Section: Discussionmentioning
confidence: 99%
“…The normal development of the hind gut is the foundation for maintaining barrier function and fermentability (32) . Recent research showed that RPS could increase the weight of the large intestine and the mucosa thicknesses of the caecum in pigs (33) .…”
Section: Discussionmentioning
confidence: 99%
“…All SCFA are claimed to act as trophic agents on caecal/colonic epithelium, but butyric seems to be the most and propionic the least efficient (Berggren et al, 1993). Another possible way of increased epithelium proliferation was indicated in a study by Whiteley et al (1996). These authors found that mucosal volume was correlated with digesta mass rather than with SCFA levels, concluding that physical stretching of the caecal/colonic epithelium might be a more important causal factor.…”
Section: Discussionmentioning
confidence: 99%
“…NaB is produced in the colon of mammals as a result of anaerobic bacterial fermentation of dietary fiber, undigested starch and proteins (Cummings, 1981;Bugaut and Bentejac, 1993;McIntyre et al, 1993;Mcintosh et al, 1996;Whiteley et al, 1996). NaB serves as an energy source of colonic epithelium.…”
Section: Introductionmentioning
confidence: 99%